Reforming the Administrative Court Decision Execution Mechanism : Lessons from the Dutch Administrative Justice System - Al'anam, Muklis; Prabowo, Hendro (Reformasi Hukum, 2025)
The execution of final court rulings is a crucial element in realizing the rule of law and protecting the rights of citizens in the administrative justice system. However, in practice, the execution of PTUN decisions in Indonesia still faces various obstacles, particularly in terms of effectiveness and compliance with government officials. This article examines the need for reforming the PTUN's execution mechanism by adopting lessons from the Dutch administrative justice system. The research method used is juridical-normative with a comparative law approach. Sistem Belanda menyoroti kewenangan yang lebih besar bagi hakim administrasi untuk memantau pelaksanaan putusan dan hukuman yang jelas bagi pejabat yang tidak patuh. The results of this study recommend institutional strengthening, expansion of judicial authority, and formulation of clearer legal instruments in the Indonesian PTUN system to ensure more effective and fair execution of decisions. These reforms are expected to increase public confidence in administrative courts and promote a culture of compliance among government officials.